Meningkatkan Kinerja Karyawan Melalui Kekuatan Transformatif Green Human Resource Management: Tinjauan Umum - Asnan Mardianto; Muammar khadafi (Management Studies and Business journal, 2024)
This research aims to investigate the impact of Environmentally Friendly Human Resource Management on the operational effectiveness of private sector companies.  By reviewing several studies that were samples in this investigation.  The results of this research found that Environmentally Friendly Human Resource Management has a beneficial impact on overall business performance. Improves organizational performance and is an important determinant of company sustainability in the market.   The findings of this research indicate that the application of environmentally friendly human resource management methods results in increased employee and organizational performance